Chemical Compositions of Essential Oils from Zanthoxylum piperitum and Anethum graveolens L. Seeds and Their Antifungal Activities on Aspergillus flavus - Chorpaka Phuangsri (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The aims of present study were to determine antifungal activity of the essential oils extracted from Anethum graveolens L. and Zanthoxylum piperitum seeds and to evaluate their potential as a food preservative. The chemical compositions of the oils were determined by GC–MS. Trans-isodillapiole (33.1%), (+)-carvone (26.0%), (-)-limonene (19.2%) and dihydrocarvone (12.3%) were the main components of A. graveolens L. oil. Whereas, the main components of Z. piperitum oil were β-phelladrene (23.2%), sabinene (14.6%) and brevifolin (11.9%). The antifungal activity of A. graveolens L. and Z. piperitum oils were tested both in solid and liquid cultures of Aspergillus flavus. The minimum inhibitory concentrations of A. graveolens L. and Z. piperitum oils, when determined on the 9th day were 2.0 µL/mL and 4.5 µL/mL, respectively. The possible mechanism of the oils antifungal activity against A. flavus is considered to be distortion of the fungal conidial heads and the reduction of hyphal diameters which could be observed by light microscopes. To confirm their target in fungal plasma membrane, their effect on ergosterol synthesis was assessed. The result indicated that the ergosterol content in the plasma membrane of A. flavus when treated with 0.25 µL/mL A. graveolens L. oil was reduced to 32%. Whereas Z. piperitum oil at 1.0 µL/mL concentration decreased the ergosterol content by 28% compared to the control.